Balancing the Grind: Social Media Entrepreneurship and Academic Success among Nigerian Undergraduates (2025)
Economic challenges in Nigeria have prompted many undergraduate students to engage in social media entrepreneurship for financial sustainability. Platforms like Facebook and Instagram provide cost-effective business opportunities. While this entrepreneurship offers benefits, it raises concerns about its impact on academic performance, especially as students often multitask between business and studies. Grounded in the Uses and Gratifications Theory, this study investigated the relationship between social media entrepreneurship and the academic performance of undergraduates. A descriptive survey research design was employed, using a randomly selected sample of 200 students from five faculties: Education, Arts, Sciences, Law, and Social Sciences at the University of Ibadan. The instrument used for data collection was the Social Media Entrepreneurship and Academic Performance Questionnaire (SMEAPQ), which included structured items eliciting responses on the social media platforms used for entrepreneurial activities, the types of social media businesses engaged in, the influence of motivation on entrepreneurial engagement, and the impact on academic performance. The reliability of the questionnaire was established through a pilot test, yielding a coefficient of 0.75. Data were analysed using both descriptive and inferential statistics. Specifically, Pearson Product-Moment Correlation (PPMC), t-tests, and means were utilized. The findings revealed that undergraduates primarily use WhatsApp (X̄=3.59), Instagram (X̄=2.97), and Telegram (X̄=2.87) for entrepreneurial ventures, focusing on influencer marketing (X̄=3.31), web development/coding (X̄=3.24), affiliate marketing (X̄=3.19), and e-commerce (X̄=3.05). A significant positive relationship was found between undergraduate motivation and engagement in social media entrepreneurship (r=.222; p<0.05), aligning with the Uses and Gratifications Theory. Additionally, a significant positive association was observed between engagement in social media entrepreneurship and undergraduates’ academic performance (r=.236; p<0.05). The study revealed that female students had better engagement in social media businesses than male students (t(195) =-3.76; p<0.05). There is a need for targeted support to help students balance business and academics, in order to foster both financial independence and academic success.